Energy Consumption, Economic Growth, and Environmental Trade Offs in Java and Bali: Nexus of Foreign Direct Investment - Jana Wiharja; Dandung Sukmawan; Andung Subekti; Sumarna Sumarna (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
Environmental degradation has become a growing concern across Indonesia's most densely populated and economically active regions. This research examines the impact of energy consumption, economic growth (GDP), and foreign direct investment (FDI) on environmental degradation measured by greenhouse gas (GHG) emissions in four provinces spanning Java and Bali, namely DKI Jakarta, West Java, East Java, and Bali, from 2000 to 2023, with reference to the Environmental Kuznets Curve (EKC). Using secondary data from BPS Statistics Indonesia, the Ministry of Energy and Mineral Resources (KESDM), the Investment Coordinating Board (BKPM), and the Ministry of Environment and Forestry (KLHK), the study employed various econometric techniques. First, the stationarity of variables was assessed through panel unit root tests. Long run connections were subsequently established using panel cointegration tests. Three panel ARDL estimation approaches, namely the Pooled Mean Group (PMG), Mean Group (MG), and Fixed Effects (FE), were employed to estimate the models, while descriptive statistics provided a summary of the data. A heterogeneous panel causality analysis was conducted to examine causal links among factors. In the short run, energy consumption and GDP exert a notable positive effect on greenhouse gas emissions. In the long run, energy consumption and FDI have a positive and significant impact, whereas GDP squared representing the inverted U shaped EKC exerts a negative and significant impact, thereby validating the EKC hypothesis. Based on these results, several environmental welfare improvement policy recommendations are proposed, including promoting green investment, monitoring and regulating foreign direct investment, fostering sustainable economic growth, and encouraging economic diversification, while also recommending the exploration of alternative economic indicators for future research